2017
DOI: 10.1097/pr9.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that dry eye is a comorbid pain condition in a U.S. veteran population

Abstract: A retrospective review of 3,265,894 veterans seen over a 5-year period demonstrates dry eye is associated with numerous chronic pain conditions implying shared mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
0
21
0
2
Order By: Relevance
“…Even though some cross-sectional/case-control studies based on patient clinics have shown positive association between DES and sleep disorders [ 15 , 16 , 17 ], there are few large-scale or nationwide studies. In particular, no findings associate DES with sleep disorders using national claim data in South Korea, because DES (International Classification of Diseases [ICD]-10 code: H04.11; new classification in 2011) was not identified in healthcare claim data before 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Even though some cross-sectional/case-control studies based on patient clinics have shown positive association between DES and sleep disorders [ 15 , 16 , 17 ], there are few large-scale or nationwide studies. In particular, no findings associate DES with sleep disorders using national claim data in South Korea, because DES (International Classification of Diseases [ICD]-10 code: H04.11; new classification in 2011) was not identified in healthcare claim data before 2011.…”
Section: Introductionmentioning
confidence: 99%
“…FM ve kuru göz ile ilgili yapılmış çok sayıda araştırma mevcuttur. Araştırmalar kuru gözün yaşlandıkça arttığını ve kadınlarda daha sık görüldüğünü ve kronik ağrı sendromlarıyla beraber sıklığının arttığını desteklemektedir (13). Yapılan çalışmada 50 yaşından sonra FM ile kuru göz birlikteliğinin arttığı, 65 yaşından sonra ise pik yaptığı gösterilmiştir (9).…”
Section: Discussionunclassified
“…We have termed this concept neuropathic ocular pain (NOP) to highlight the fact that pain generation can initiate from nerves on the ocular surface (cornea and conjunctiva) or from secondary and tertiary neurons that connect the ocular surface to the brain. Risk factors for the development of NOP include chronic overlapping pain conditions and migraine, and central sensitization is thought to link the entities 42, 43 .…”
Section: Aspects To Be Considered In Patients With Dry Eye Disease Symentioning
confidence: 99%